Evaluasi Kesesuaian Lahan untuk Tanaman Terung (Solanum Melongena L.) di Kecamatan Tabongo Kabupaten Gorontalo - Laila Latukunsina; Muhammad Arief Azis; Yunnita Rahim (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
This study was conducted to evaluate land suitability for eggplant (Solanum melongena L.) cultivation in Tabongo District, Gorontalo Regency. The land suitability evaluation aimed to identify land characteristics and qualities, determine actual and potential land suitability classes, and assess limiting factors for eggplant cultivation. The research employed a survey method using a physiographic approach. Land suitability analysis was performed by matching land characteristics and qualities—derived from field observations, climate data, and laboratory soil analysis—against eggplant suitability criteria based on Ritung et al. (2011). Analyzed parameters included temperature, rainfall, air humidity, drainage, soil texture, effective soil depth, cation exchange capacity (CEC), soil pH, organic C content, total N, P₂O₅, K₂O, slope gradient, erosion hazard level, surface stones, and rock outcrops. The results indicate that actual land suitability classes for eggplant in Tabongo District range from marginally suitable (S3) to not suitable (N), with primary limiting factors including rainfall, soil texture, effective soil depth, nutrient availability, erosion hazard, slope gradient, surface stones, and rock outcrops. Based on the evaluation results and potential improvement measures, the potential land suitability classes in Tabongo District remain in the marginally suitable (S3) to not suitable (N) categories, covering an area of ​​2,357.76 hectares.